Analysis and Evaluation of Storage Systems Using the ABC Classification and Periodic Review Method at Supermarket in Semarang City - Manasya Khulafa Alief Rahman; Zaenal Abidin (Journal of Advances in Information Systems and Technology, 2024)
The warehouse section is one of the parts that must exist in the company, especially for manufacturing or retail companies. Therefore, companies usually implement a storage system which is a policy to control, supervise, and determine the level of goods that need to be maintained. In addition, companies also use supply chain management to control the number of incoming and outgoing goods more effectively and efficiently. This is because the company only has limited warehouse storage space, so the amount of goods stored must also be in accordance with company needs. Including one of the retail companies in Semarang City, it is PT Inti Cakrawala Citra or can be called Indomaret Group which built a supermarket namely Indogrosir which has been established for almost 30 years and a lot of research has been done there, so it has a strong company system, including in the warehouse section. Based on this explanation, this study aims to analyze by implementing the proposed method using ABC Classification and Periodic Review on the storage system and evaluation based on the results obtained. This research uses a mixed-method approach with interview and documentation studies as data collection methods. The results of the interview that have been conducted prove that Indogrosir has a strong storage system and the results of the documentation study also show that the data successfully obtained are 19,872 with six different types of goods in the period October 2022 to August 2023. The result of data processing is the type of tabbacco which amounts to 274 data selected as a sample and results in the calculation of the total storage cost on one of the product codes with the company's method of IDR 10,888,505,214 and the proposed method of IDR 4,473,946, so that the implementation of the proposed method is more optimal. This is due to one of the variables in the company's method that uses purchase data or can be called capital for cashflow in the company, so it has much greater results. In addition, the proposed method also provides other outputs, such as the number of reorders, the amount of safety stock, and a high level of service level by implementing the proposed method that can help companies in managing stock items.